IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KOLABORASI MURID KELAS II SDN SUNGAI MIAI 11 BANJARMASIN - Ferda, Selma; Aulia, Rahmat; Alvina; Pratama, Noval Nanda; Setiawan; Novitawati; Sholehah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low levels of critical thinking and collaboration skills among students were identified as key issues in mathematics instruction in Class IIA at SDN Sungai Miai 11 Banjarmasin. This Classroom Action Research (CAR) aimed to enhance students' critical thinking and collaboration skills through the implementation of the Problem-Based Learning model. The study was conducted over three cycles involving 19 students from Class IIA at SDN Sungai Miai 11 Banjarmasin during the even semester of the 2025/2026 academic year. Qualitative data were collected using student skill observation sheets, while quantitative data were analyzed using a classical percentage formula. The results demonstrated improvement across each cycle. Class-wide critical thinking skills rose from 50% (Cycle I) to 67% (Cycle II) and reached 87% (Cycle III), achieving the